Aplikasi Motif Batik Tradisional Surakarta Pada Produk Keramik Dinding Dengan Teknik Glasir - Prima Yustana; Nofrijon Sofyan; Veronika Kristanti Putri Laksmi (Institut Seni Indonesia Surakarta, 2013)
This research was aimed at creating a new prototype ofdecorative wall ceramic characterized by local cultural character.The proposed work was motivated by the traditional batik characterizedby local style of Surakarta on the decorative wall ceramicby using glaze coloring techniques. An experimental study withseveral stages of material testing, firing, and glazing temperaturesas well as coloring motif with glaze techniques has beenperformed. The successful application of the traditional batik onthe ceramic wall with a glaze technique is expected to contributeprimarily to the creative industries. In addition, this decorativewall ceramic products would be able to support the opportunitiesto create new jobs based on the creative economy, in line withthe government program in addressing the unemployment. Theresulting prototype of decorative ceramic wall is also expected toprovide a solution to overcome local art and cultural identity degradationphenomena. Finally, in particular, the results of this studyare expected to (1) generate the description and identification ofthe problems arising in the process of decorative wall ceramicmaking by using glaze technique, (2) provide a new alternativeproducts, and (3) support the era of the creative industry with thecreation of new products that carry local cultural character andas a solution to the creation of a new field for the unemployment.Keyword: Wall Ceramic, Glazing Teqnique, Traditional Batik Surakarta